Nobiletin Induces Ferroptosis in Human Skin Melanoma Cells Through the GSK3β-Mediated Keap1/Nrf2/HO-1 Signalling Pathway - Feng, Senling; Zhou, Yongheng; Huang, Hongliang; Lin, Ying; Zeng, Yifeng; Han, Shanshan; Huang, Kaikai; Liu, Quanzhi; Zhu, Wenting; Yuan, Zhongwen; Liang, Baoying (Frontiers in Genetics, 2022)
Melanoma is an aggressive malignant skin tumour with an increasing global incidence. However, current treatments have limitations owing to the acquired tumour drug resistance. Ferroptosis is a recently discovered form of programmed cell death characterised by iron accumulation and lipid peroxidation and plays a critical role in tumour growth inhibition. Recently, ferroptosis inducers have been regarded as a promising therapeutic strategy to overcome apoptosis resistance in tumour cells. In this study, we reported that nobiletin, a natural product isolated from citrus peel, and exhibited antitumour activity by inducing ferroptosis in melanoma cells. Subsequently, we further explored the potential mechanism of nobiletin-induced ferroptosis, and found that the expression level of glycogen synthase kinase 3β (GSK3β) in the skin tissue of patients with melanoma was significantly reduced compared to that in the skin of normal tissue. Additionally, nobiletin increased GSK3β expression in melanoma cells. Moreover, the level of Kelch-like Ech-associated protein-1 (Keap1) was increased, while the level of nuclear factor erythroid 2-related factor 2 (Nrf2), and haem oxygenase-1 (HO-1) was decreased in nobiletin-treated melanoma cells, suggesting that the antioxidant defence system was downregulated. Furthermore, knockdown of GSK3β significantly reduced nobiletin-induced ferroptosis and upregulated the Keap1/Nrf2/HO-1 signalling pathway, while the opposite was observed in cells overexpressing GSK3β. In addition, molecular docking assay results indicated that nobiletin showed strong binding affinities for GSK3β, Keap1, Nrf2, and HO-1. Taken together, our results demonstrated that nobiletin could induce ferroptosis by regulating the GSK3β-mediated Keap1/Nrf2/HO-1 signalling pathway in human melanoma cells. Hence, nobiletin stands as a promising drug candidate for melanoma treatment with development prospects.